Measuring the relation between “Political Justice” and “Political Freedom” with an Emphasis on the Holy Qur’an - Seyyed Kazem SeyyedBaqeri; Batol MollaShafii (‫سیاست متعالیه‏, 2017)
The present article, through relation measurement of “Political Justice” and “Political Freedom” by emphasizing the Holy Qur’an is after clarification of the two concepts, stressing the fact that any justice has freedom within itself as regards to recent relation and types of relations and imaginable relationships like contradiction and partition, equality, absolute publicity and the public in general. This happens because justice means fulfilment of public rights and freedom is considered as one of its clear-cut applications. Henceforth, just as some of applications of freedom are justice (such as freedom of choice), so some freedoms (like freedom of chaos) fail to result in justice. By elucidating these relationships, the hypothesis emphasized is that when freedom is bound to justice and interaction of these two concepts considering the central meaning of public rights fulfilment in political justice and freedom, there is the possibility that political justice paves the ground for political freedom emerging in the community.